(untitled) (The Peerian Journal, 2022)
The solubility of substances in a highly critical medium at high pressure and temperature is studied, the main representatives of such media, primarily highly critical carbon dioxide, are given, their physicochemical properties, advantages and disadvantages are considered. The use of supercritical CO2 as a reaction medium, monomer, and catalyst in the synthesis of predominantly condensation-type polymers is analyzed.